Isolation of Facultative Anaerobic Bacterial Pathogens from Canned Food and Use of Lactobacillus Plantarum as A Bio-Control Agent: Facultative Anaerobic Bacterial Pathogens from Canned Food - Malik, Khudija; Ibne Shoukani, Hussan; Hassan, Sabayyel; Bibi, Saima; Bano, Syeda Asma (Pakistan BioMedical Journal, 2023)
Preserved foods can play a significant role in causing food poisoning when they are not handled, processed, or stored properly. Objective: To investigate facultative anaerobic foodborne bacterial pathogens from canned foods and to control their growth Lactobacillus plantarum was used as a bio-control agent. Methods: Different canned food samples were collected to isolate and identify facultative anaerobic bacterial pathogens. Results: Out of n=65 samples, n=13 samples cultured positive as facultative anaerobes. They were further confirmed with biochemical and molecular identifications as foodborne bacterial pathogens with a ratio of 62% Escherichia coli, 30% Salmonella typhimurium, and 8% Vibrio cholerae. During bio-control studies, the results revealed possible inhibition of facultative anaerobic bacterial pathogens by using purified compounds of Lactobacillus plantarum. Conclusions: The use of probiotics in canned foods requires careful consideration, as factors such as the specific strain, food matrix, processing conditions, and storage practices can influence its effectiveness.